CONSTRAINED MULTIFACILITY LOCATION PROBLEMS – A REVIEW - Santra, Ajit Kumar (International Journal of Industrial Engineering: Theory, Applications and Practice, 2020)
The main aim of this review is to examine the work of various authors relevant to facility location problem. This critical examination of the existing work in this area will help the various researchers in setting forth the motivation of further study of the facility location problems under different perspectives. For convenience it has been discussed the topics under narration in sequence as follows: (a) Problems with Euclidean Norm, (b) Problems with Squared Euclidean Norm, (c) Problems with Rectilinear Norm and (d) Further Related Work (which do not fall under norm wise classification). In each category, the facility location problems have been discussed under (i) Deterministic Model and (ii) Uncertain Model. In addition, we have also provided a few related survey papers under the category (d). It is found that only a few researchers have done some work involving area constraints even though, it is a very important aspect of each and every location problem. Finally, we have provided the future direction of research work in the field. We do believe that this review will certainly facilitate further research work in the area.